Research Progress on the Corrosive Environment Large-Scale Evolution for Nuclear Waste Container - Zhang, Qichao; Jiang, Yishan; Zhao, Xin; Chen, Juna; Xia, Dahai; Zhang, Binbin; Duan, Jizhou (Frontiers in Materials, 2022)
After a nuclear waste container buried 500–1,000 m underground, it gradually experiences the dual effects of groundwater infiltration and the decay heat of radioactive nuclear waste. The decay and heat release of nuclear waste will also result in temperature stress. At the same time, the groundwater will gradually saturate the buffer/backfill materials which will produce expansion stress, thus forming a typical thermal–water–stress multi-coupling environment in the geological disposal, forming the environment where the corrosion could happen. In comparison, the information obtained through laboratories, field tests, and natural simulations are limited. However, numerical simulation is very important to predict the changes of a near-field environment. On one hand, the numerical simulation can verify the corresponding experimental data in the early stages; on the other hand, it can also predict the long-term corrosion environment change. This article mainly summarizes the large-scale evolution of a typical corrosion environment obtained by numerical simulation under different deep geological conditions in various countries, focusing on the effects of temperature, saturation, oxygen content, and radiation, which provide a reference for the research on the evolution of important corrosion environments on the surface of a nuclear waste container.